Chinese Guidelines for the Diagnosis and Treatment of Heart Failure 2024 - Editorial Board of Chinese Journal of Cardiology; Hanjia Gao (Cardiology Discovery)
Abstract. In the past 6 years, significant breakthroughs have been achieved in the treatment of heart failure (HF), especially in drug therapy. The classification of chronic HF and the treatment methods for HF and its complications are also constantly being updated. In order to apply these results to the diagnosis and treatment of patients with HF in China and further improve the level of diagnosis and treatment of HF in China, the HF Group of Chinese Society of Cardiology, Chinese Medical Association, Chinese College of Cardiovascular Physician, Chinese HF Association of Chinese Medical Doctor Association, and Editorial Board of Chinese Journal of Cardiology have organized an expert group and update the consensus and evidence-based treatment methods in the field of HF based on the latest clinical research findings at home and abroad, combined with the national conditions and clinical practice in China, and referring to the latest foreign HF guidelines while maintaining the basic framework of the 2018 Chinese Guidelines for Diagnosis and Treatment of HF.